Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/molecules25204806
|View full text |Cite
|
Sign up to set email alerts
|

Computational Design of Nitrile Hydratase from Pseudonocardia thermophila JCM3095 for Improved Thermostability

Abstract: High thermostability and catalytic activity are key properties for nitrile hydratase (NHase, EC 4.2.1.84) as a well-industrialized catalyst. In this study, rational design was applied to tailor the thermostability of NHase from Pseudonocardia thermophila JCM3095 (PtNHase) by combining FireProt server prediction and molecular dynamics (MD) simulation. Site-directed mutagenesis of non-catalytic residues provided by the rational design was subsequentially performed. The positive multiple-point mutant, namely, M10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Such creation of hydrophobic cores was observed during analysis of mesophilic and thermophilic proteins sequences (Haney et al 1999 ; Saelensminde et al 2009 ). During the process of MD simulations, when residue is mutated into hydrophobic amino acid, the hydrophobic core can be formed, such as in neurotensin receptor (Lee et al 2015 ), enzymes like trehalose synthase (Chen et al 2021 ), and nitrile hydratase (Cheng et al 2020 ; Guo et al 2021 ). The semi-rational design approach established in the present study sheds light on the future engineering of other industrial attractive SPases, such as the one from Bifidobacterium adolescentis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such creation of hydrophobic cores was observed during analysis of mesophilic and thermophilic proteins sequences (Haney et al 1999 ; Saelensminde et al 2009 ). During the process of MD simulations, when residue is mutated into hydrophobic amino acid, the hydrophobic core can be formed, such as in neurotensin receptor (Lee et al 2015 ), enzymes like trehalose synthase (Chen et al 2021 ), and nitrile hydratase (Cheng et al 2020 ; Guo et al 2021 ). The semi-rational design approach established in the present study sheds light on the future engineering of other industrial attractive SPases, such as the one from Bifidobacterium adolescentis.…”
Section: Discussionmentioning
confidence: 99%
“…The semi-rational design combines the benefits of directed evolution and rational design and is suitable for modifying proteins without high-throughput determination methods and structure–function understanding (Chica et al 2005 ). Many successful examples have reported that changing a few amino acids can significantly improve the protein thermostability by semi-rational design strategies (Cheng et al 2020 ; Roth et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Improving thermostability may decrease the enzyme activity because it could change the flexibility of the structure ( Xu et al, 2020 ). But, there are cases in which the thermostability was improved and the enzyme activity was increased by using FireProt ( Cheng et al, 2020 ; Xia et al, 2021 ). Protein analysis tools such as Rate4Site, FoldX, and Rosetta design were assembled to offer a reliable design of stable multiple-point mutants in FireProt ( Musil et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Two distinct methodologies were involved in the semi-rational design: sequence-based enzyme redesign and structure-based enzyme redesign ( Xiong et al, 2021 ). Proteins without a crystal structure or high-throughput determination methods could be redesigned for higher activity and better thermal stability by semi-rational design strategies ( Nakano et al, 2018 ; Cheng et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Conventional full-atomic MD simulations [ 47 , 48 , 49 ] were performed for human 15LOX-2 (PDB id: 4NRE [ 20 ]) and 15LOX-2/PEBP1 complex (PDB ids: 4NRE and 1BEH [ 50 ]), with a bound substrate (SAPE), in the presence of randomly distributed nitric oxide and oxygen molecules with different ratios, such as 1:1 (five of each), 1:3, and 3:1. Multiple MD runs (see Supplementary Table S1 ) of 150 ns with different initial spatial distributions of NO ● and O 2 molecules were performed for each structure (15LOX-2 and its complex with PEBP1) using the NAMD [ 51 ] software with the CHARMM [ 52 ] force field and 2 fs time steps.…”
Section: Methodsmentioning
confidence: 99%